1999
DOI: 10.1073/pnas.96.21.12204
|View full text |Cite
|
Sign up to set email alerts
|

Late maturation of visual spatial integration in humans

Abstract: Visual development is thought to be completed at an early age. We suggest that the maturation of the visual brain is not homogeneous: functions with greater need for early availability, such as visuomotor control, mature earlier, and the development of other visual functions may extend well into childhood. We found significant improvement in children between 5 and 14 years in visual spatial integration by using a contour-detection task. The data show that long-range spatial interactions-subserving the integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
226
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(254 citation statements)
references
References 41 publications
25
226
2
1
Order By: Relevance
“…Studies of adult spatial updating behaviours have capitalised on the triangle-completion task in order to measure both factors working together, and we here report an experiment that, for the first time, uses this task in children. We also sought to examine if there was a developmental change in path integration abilities -this was motivated by a number of suggestions that children demonstrate particular advancement in their spatial abilities around the age of 6-7 years (Kovas, Kozma, Fehér & Benedek, 1999;Plumert & Spencer, 2007;Shemyakin, 1962). Since previous studies have found that the calculation of heading is more likely to dissociate between participant groups than distance (Smith et al, 2010), we predicted that heading estimations may improve faster between 5 years and 7 years than distance estimations.…”
Section: Development Of Path Integrationmentioning
confidence: 99%
“…Studies of adult spatial updating behaviours have capitalised on the triangle-completion task in order to measure both factors working together, and we here report an experiment that, for the first time, uses this task in children. We also sought to examine if there was a developmental change in path integration abilities -this was motivated by a number of suggestions that children demonstrate particular advancement in their spatial abilities around the age of 6-7 years (Kovas, Kozma, Fehér & Benedek, 1999;Plumert & Spencer, 2007;Shemyakin, 1962). Since previous studies have found that the calculation of heading is more likely to dissociate between participant groups than distance (Smith et al, 2010), we predicted that heading estimations may improve faster between 5 years and 7 years than distance estimations.…”
Section: Development Of Path Integrationmentioning
confidence: 99%
“…The Contour Integration Test (Kovacs et al, 1999) was administered on three consecutive days as an index of learning and visual context processing. It consists of 15 cards which contain varying numbers of Gabor elements against a uniform gray background (see Fig.…”
Section: Controlled Oral Word Association Test (Cowat)mentioning
confidence: 99%
“…More complex perceptual abilities requiring integration of information over space have more extended developmental time courses. For example, children younger than about age 3 are unable to perform a contour integration task, and their performance continues to improve into the teenage years (Pennefather et al, 1999;Kovács et al, 1999). Similarly, monkeys are unable to perform contour integration before 5-6 months and continue to improve into at least the second postnatal year (Kiorpes & Bassin, 2003).…”
Section: Introductionmentioning
confidence: 99%